Social Media, Conspiracy Beliefs, and COVID-19 Vaccines: A Survey Study of Emerging and Middle-Aged Adults in the United States - Gillianne R. Nugent; Dina Anselmi; Brian N. Chin (Social Sciences)
This study examined the connections between social media use and behaviors, COVID-19 vaccine conspiracy beliefs, and COVID-19 vaccine uptake in 809 emerging and middle-aged adults. Emerging adults reported more overall social media use, active and passive social media behaviors, and use of most platforms (i.e., Instagram, Snapchat, TikTok, Twitter/X, Reddit, and YouTube), whereas middle-aged adults reported more Facebook use and higher vaccine uptake. COVID-19 vaccine conspiracy beliefs were linked to lower vaccine uptake, with this association unexpectedly stronger among individuals who reported less social media use and fewer active and passive social media behaviors. Active social media behaviors were associated with stronger vaccine conspiracy beliefs, whereas passive social media behaviors and overall use did not show a similar association. Exploratory analyses of platform-specific effects revealed nuanced patterns: TikTok use was associated with stronger vaccine conspiracy beliefs, Instagram use was associated with higher vaccine uptake, and Snapchat use was associated with lower vaccine uptake. Our findings highlight the complex, platform-specific influences of social media use and behaviors on COVID-19 vaccine conspiracy beliefs and vaccine uptake. Future studies are needed to investigate the role of specific social media platforms in spreading, perpetuating, or countering misinformation about the COVID-19 vaccine.